KONSEP DADI WONG MENURUT PANDANGAN WANITA JAWA - Atik Triratnawati (Humaniora, 2005)
A successful person is always related with wealth and life satisfaction. Meanwhile the term successful person in different ethnic groups has different meaning and interpretation. The concept about dadi wong (being successful person) exists in Javanese culture which is always mentioned to describe the success of person in his or her life. The article will discuss this .The research was conducted in Yogyakarta on 1995 using a qualitative research method with in-depth interview. The research was held among selected (20) Javanese women aged 17-68 years, which had different education and socio economic status. Dadi wong requires economic, religious, moral, psychological and physical aspects. Other aspects includes gender ideology and culture. According to the Javanese concept dadi wong means merely economic aspect. The ideal concept of Dadi wong should be combined with economic (economic independence, income), culture (socio-status, marriage, family life, education, good in social relation, meaningful to other), morality/religion (religiosity, good moral) and psychology (independence, happiness).